Impact of Protocol Amendments, Personnel Experience and Social Determinants of Health on Study Protocol Adherence in Clinical Trials with Combination Products - Cilley, K. N.; Kaliaev, A. O.; Malikova, M. A. (Therapeutic Innovation & Regulatory Science, 2025)
The amendments to the International Council for Harmonization (ICH) Good Clinical Practice (GCP) E8 guidelines were introduced to enhance clinical trial quality, patient safety, and efficiency through a more patient-centric, risk-based approach. This study investigates the impact of various study risk factors such as protocol amendments, informed consent changes, protocol complexity, and social determinants of health (SDOH) on protocol deviations and patient retention in clinical trials involving combination products.